Sencha Touch 2 Mobile JavaScript framework - Clark, John Earl; Johnson, Bryan P. (Community experience distilled, 2013)
In Detail Sencha Touch is a versatile HTML5-based framework for developing mobile web apps. Sencha Touch 2 has raised the bar for developing rich mobile web applications with HTML5. Using this framework you can develop mobile web apps that look and feel like native apps on iOS, Android, Blackberry, and Windows Mobile. It is built for enabling world-class user experiences. "Sencha Touch 2 Mobile JavaScript Framework" is a step-by-step tutorial that will show you how to use Sencha Touch to produce attractive, exciting, native-quality, user friendly, easy-to-use mobile applications, that will keep your visitors coming back for more. There is sample code provided and explained with essential screenshots for better and quicker understanding. "Sencha Touch 2 Mobile JavaScript Framework" will provide you with a hands-on approach to learning the language, taking you through the basic concepts and designs, to building a complete application from scratch. We start with a foundation of JavaScript basics and work our way through the various components and features of Sencha Touch. We will explore how to leverage the Sencha Cmd utility to create applications quickly and cleanly. We will talk about how to get data in and out of your application, how to create new styles and themes, and even how to compile an application for sale on the various app stores. "Sencha Touch 2 Mobile JavaScript Framework" will make you an expert application developer, using clear examples, code, and concepts. Approach Full of explained code and enriched with screenshots, this book is the practical way to take your Sencha Touch skills to the next level. Who this book is for If you want to gain practical knowledge for using the Sencha Touch mobile web application framework, and you are familiar with HTML and CSS, then this book is for you. It is assumed that you know how to use touchscreens, touch events, and mobile devices such as Apple iOS and Google Android